Investigation of extraction methods on the antibacterial activity of Moringa oleifera seed extract - Muyibi, Suleyman Aremu; Idris Abolore, Munirat; Jamal, Parveen; Jami, Mohammed Saedi; Abdulkarim, Mohd Ismail (2012)
Moringa Oleifera is one of the most extensively studied plant materials for water treatment. It is usually referred to as a miracle plant because of its multipurpose uses. Several studies have revealed that it possesses antibacterial activity against harmful bacteria. This study investigates the effect of two extraction methods; aqueous extraction and 1M salt extraction of Moringa Oleifera seed extracts against Escherichia coli, Pseudosomonas aeruginosa, Bacillus subtilis and Staphylococcus aureus strains using the agar well diffusion method. The effects of various concentrations of the seed extracts against the selected bacterial strains were carried out and an attempt was made to find the Minimum Inhibitory Concentration (MIC) as well as the Minimum Bactericidal Concentration (MBC) of the extracts. The results of both extraction methods showed that Moringa Oleifera seed extracts have a strong antibacterial activity against all the bacterial strains. The diameter of inhibition zone ranges from 13mm to 30mm for the two extraction methods. However, the salt extract showed a higher inhibition of 30mm at extract concentration of 5mg/ml against all the bacterial strains. The MIC of the salt extract was obtained at 1.562mg/ml for Escherichia coli, 3.125mg/ml for Pseudosomonas aeruginosa, 1.562mg/ml for Bacillus subtilis and 3.125mg/ml for Staphylococcus aureus while the MBC for the salt extract was obtained at 6.25mg/ml, 6.25mg/ml, 12.5mg/ml, 12.5mg/ml for Escherichia coli, Pseudosomonas aeruginosa, Bacillus subtilis and Staphylococcus aureus respectively. The results of these findings show that both aqueous and salt extracts of Moringa Oleifera seed have a significant antibacterial property that can be utilized for disinfection purposes for drinking water. Keywords: Agar well diffusion, antibacterial activity, Moringa Oleifera, Minimum Inhibitory Concentration, Minimum Bactericidal Concentration